OCR A Level Further Mathematics Year 1 (AS). - Baldwin, Claire (Hodder Education Group, 2017)
Exam Board: OCRLevel: A-levelSubject: MathematicsFirst Teaching: September 2017First Exam: June 2018 Grow your students' confidence in applying mathematical techniques to solving problems with resources developed specifically for the OCR specification subject experts and in conjunction with MEI (Mathematics in Education and Industry).- Develop reasoning and problem-solving skills with practice questions and differentiated exercises that build mathematical techniques.- Help students to overcome misconceptions and develop insight into problem-solving with annotated worked examples.- Build conn.